2022
DOI: 10.3171/case22431
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic cervical spine subarachnoid hemorrhage with hematoma and cord compression presenting as Brown-Séqüard syndrome: illustrative case

Abstract: BACKGROUND Spinal hematomas are a rare entity with broad etiologies, which stem from idiopathic, tumor-related, and vascular malformation etiologies. Less common causes include traumatic blunt nonpenetrating spinal hematomas with very few cases being reported. In the present manuscript presents a case report and review of the literature of a rare traumatic entity of a cervical subarachnoid hematoma in association with Brown-Séquard syndrome in a patient on anticoagulants. Searches were performed on PubMed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Patient’s primary risk factors included history of factor X inhibitor anticoagulation and trauma. The literature review suggested that there are independent risk factors for the development of CEH [ 5 ]. One recent phenomenon is the prevalence of using anticoagulants among the aging population for conditions such as atrial fibrillation, cerebrovascular diseases, and coronary artery disease [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patient’s primary risk factors included history of factor X inhibitor anticoagulation and trauma. The literature review suggested that there are independent risk factors for the development of CEH [ 5 ]. One recent phenomenon is the prevalence of using anticoagulants among the aging population for conditions such as atrial fibrillation, cerebrovascular diseases, and coronary artery disease [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature review suggested that there are independent risk factors for the development of CEH [ 5 ]. One recent phenomenon is the prevalence of using anticoagulants among the aging population for conditions such as atrial fibrillation, cerebrovascular diseases, and coronary artery disease [ 5 ]. Disruption of coagulative properties, resulting from iatrogenic and paraneoplastic factors, also constitute increased risks of the development of hematoma or bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations